Role of Colchicine Treatment in Tumor Necrosis Factor Receptor Associated Periodic Syndrome (TRAPS): Real-Life Data from the AIDA Network. (27th May 2020) - Vitale, Antonio; Sota, Jurgen; Obici, Laura; Ricco, Nicola; Maggio, Maria Cristina; Cattalini, Marco; Ruscitti, Piero; Caso, Francesco; Manna, Raffaele; Viapiana, Ombretta; Caggiano, Valeria; Emmi, Giacomo; et al.
Abstract : Objective . To analyze the potential role of colchicine monotherapy in patients with tumor necrosis factor receptor associated periodic syndrome (TRAPS) in terms of control of clinical and laboratory manifestations. Methods . Patients with TRAPS treated with colchicine monotherapy were retrospectively enrolled; demographic, clinical and therapeutic data were collected and statistically analysed after having clustered patients according to different times at disease onset, penetrance of mutations, dosage of colchicine, and different disease manifestations. Results . 24 patients (14 males; 15 with pediatric disease onset) treated with colchicine monotherapy were enrolled. Colchicine resulted in a complete response in 3 (12.5%) cases, partial response in 14 (58.3%) patients, and lack of response in 7 (29.2%) patients. There were not significant differences in colchicine response between pediatric and adult disease onset (p = 0.42 ), between low- and high-penetrance mutations (p = 0.62 ), and according to different dosages (p = 0.66 ). No significant differences were identified in the frequency of specific disease manifestations between patients experiencing any response to colchicine and patients with lack of response. Conclusions . Colchicine monotherapy is useful in a low percentage of TRAPS patients; nevertheless, it could be attempted in patients with milder phenotypes and at a lower risk of developing reactive amyloidosis.